Torpedo Swimrun Cape Town: understanding athletes, evaluation of race rules and assessing predictors of performance of a novel sport - Geromont, Christina (Department of Human Biology, 2021)
Aims: The first aim was to describe the characteristics and demands of the Torpedo SwimRun Cape 2019 race. The second aim was to determine predictors of race performance, by using entry, result and questionnaire data. Objectives: The first objective was to explore distributions of age (y), sex, 1km pool swimming time (mm:ss), 5km road running time (mm:ss), competency level (Likert scale), estimated race finishing time (hh:mm), training habits (min/week and sessions/week), background sport (type), equipment used (type), wave selection (athletes select if they want to start in a slow, medium or fast wave)(type), total and segment race times (mm:ss) and questionnaire scores of race participants. The second objective was to analyze segment and race result times, 5km run times, 1km swim times and ocean knowledge questionnaire results. Results: In total, there were 99 participants (288 athletes took part in the race) of which 36% were female and 64% were male. Each team in the Torpedo SwimRun Cape must consist of two athletes. Of the athletes, 53% were entered in male teams, 30% in mixed teams (a male and a female per team) and 17% entered in female teams. The median age was 41 years with an interquartile range (IQR) of 19 years. The mean race time was 174:15 mm:ss (± 29:51 mm:ss). Athletes trained on average 7 sessions/week (IQR 7 sessions/week), and 435 min/week (IQR 345 min/week). The median ocean knowledge score (OKQ) was 9 (IQR 4). Athletes' self-reported current 5km road running time was on average 25:00 mm:ss (IQR 07:41 mm:ss) and their current 1km pool swimming time was 18:00 mm:ss (IQR 07:02 mm:ss). Total race time was significantly associated with current 5km road running time ( = 0.488, p = 0.001), current 1km pool swimming time ( = 0.607, p = 0.001) and OKQ score ( = -0.349, p = 0.003). These three variables were also used to predict total race time. The over-all linear regression model was found to be significant (R2 = 0.514, p = 0.001). Conclusion: The athletes that participated in the Torpedo SwimRun Cape 2019 display a large variance in their training habits, particularly their training loads. It was found that the performance in this SwimRun race was not only dependent on how trained athletes were, but 4 also their ocean knowledge. Ocean knowledge is a learned skill and not necessarily attained by swimming in the ocean more (training open-water swimming was not associated with OKQ score). The OKQ questionnaire showed that better scores were associated with faster total racing time. The model used to predict performance accounted for approximately half of the variation seen in total race time. There is a clear need to further understand how performance is affected in SwimRun races. Repeat studies should be done to investigate different training strategies (also taking an athlete's team partner into account), the effect of various environmental exposures and how different equipment influence racing.